2005
DOI: 10.1103/physrevb.71.195417
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of single-wall carbon nanotubes in aqueous surfactant suspensions: A Raman study

Abstract: Aqueous suspensions of bundles and individual singlewall carbon nanotubes were prepared with the help of surfactants. We study the changes in the Raman spectra of the suspensions with respect to powders, and of exfoliated tubes with respect to bundles. The radial breathing modes (RBM) upshift in suspensions because of the internal pressure of the liquid. By contrast, no shift is observed in the RBM spectra after exfoliation in the suspensions. However, we demonstrate a selectivity of the exfoliation process fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 32 publications
6
54
0
Order By: Relevance
“…whether the SWCNTs are present as individual tubes wrapped in a surfactant, isolated on a substrate surface, or in the form of bundles. 23 Recently, Izard et al 33 reported on an upshift of RBM wavenumbers in solubilized bundles or isolated tubes with respect to those measured in dry powders. However, in those cases where the RBM resonance profiles of individual vs bundled SWCNTs were compared, the same RBM wavenumbers have been found.…”
Section: Overview Of Raman Modes In Swcntsmentioning
confidence: 99%
“…whether the SWCNTs are present as individual tubes wrapped in a surfactant, isolated on a substrate surface, or in the form of bundles. 23 Recently, Izard et al 33 reported on an upshift of RBM wavenumbers in solubilized bundles or isolated tubes with respect to those measured in dry powders. However, in those cases where the RBM resonance profiles of individual vs bundled SWCNTs were compared, the same RBM wavenumbers have been found.…”
Section: Overview Of Raman Modes In Swcntsmentioning
confidence: 99%
“…Recently, various studies reported upshifts of x vib due to environmental changes such as the interactions with surfactants that were used for the solubilization of CNTs. [15] By using a bile salt, sodium deoxycholate (DOC), to solubilize the CNTs in D 2 O, the different spectral features of empty and water-filled CNTs can be very well resolved. A 2D map of RRS spectra as a function of laser wavelength is shown in Figure 1 for two such samples.…”
mentioning
confidence: 99%
“…The relative intensity of Dband in the Raman spectra, which correlates with defects in SWCNT structure, [17] has no significant change owing to the treatment. From the above phenomena, we can conclude the treatment method has not damaged the SWCNT electronic structure.…”
Section: Resultsmentioning
confidence: 98%